Case Report: Long Progression-Free Survival of Immunotherapy for Lung Adenocarcinoma With Epidermal Growth Factor Receptor Mutation - Peng, Jianfeng; Zhao, Xianguang; Zhao, Kaikai; Meng, Xiangjiao (Frontiers in Oncology, 2021)
Background Immune checkpoint inhibitors (ICIs) have been clinically proven to be efficient in non-small cell lung cancer (NSCLC). However, it has also been found that immunotherapy is not effective for all patients. For instance, some patients with epidermal growth factor receptor (EGFR) mutation tumors have a low overall response rate to ICIs. As a result, we retrospectively analyzed the efficacy of anti-programmed death-ligand 1 (anti-PD-L1) blockade (atezolizumab) treatment for a patient with EGFR mutation, and we explored the interaction between immunotherapy and EGFR mutations in NSCLC. Case Presentation A patient, 62-year-old non-smoking female, with lung adenocarcinoma was initially misdiagnosed as EGFR wild type and received a third-line treatment with atezolizumab, experiencing partial response (PR) and progression-free survival (PFS) for 23 months. She had later been confirmed with EGFR L858R mutation prior to taking atezolizumab. On top of that, the patient developed T790M mutation after being administered with atezolizumab instead of EGFR tyrosine kinase inhibitors (TKIs). She started with osimertinib, although the lesion continued to progress. Tumor mutational burden (TMB), PD-L1 expression, and tumor-infiltrating lymphocytes (TILs) had been tested for further analysis. Conclusion The case report and literature review indicate that ICIs might be more effective for L858R mutation than for other EGFR mutant subtypes, which correlates with certain potential predictors such as TMB and concurrent PD-L1 plus CD8+ TIL expression. However, there is no report on progression from non-primary EGFR T790M mutation to T790M mutation of patients who neither previously suffered from EGFR-TKIs nor responded to osimertinib. This case report will offer some information to guide the investigation on how to identify those who can benefit from immunotherapy and those who do not respond to EGFR-TKIs among the patients with EGFR mutations.